2017
DOI: 10.3892/mmr.2017.7657
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378b regulates α-1-type 1 collagen expression via sirtuin 6 interference

Abstract: Ultraviolet (UV) light mediates skin aging and induces destruction of the dermis by modulating the expression levels of extracellular matrix‑associated genes, including collagen and matrix metalloproteinases. Sirtuin 6 (SIRT6), a member of the sirtuin family of proteins, regulates collagen metabolism and is an established anti‑aging protein. However, the exact underlying mechanism by which SIRT6 expression is regulated in dermal fibroblasts during the aging process is unclear. The present study demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Ma found that miRNA-29 family members control the immune system and host-pathogen interactions and influence cytokine (IFN, TNF, and interleukin) signaling in response to bacterial and viral infections [38]. The miR-378 family was observed to influence cell proliferation, and to suppress tumour growth and angiogenesis through various signaling pathways and cytokine production patterns [39][40][41][42][43][44][45]. Our findings show that miR-29a increases IFN-β production and decreases the expression of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Ma found that miRNA-29 family members control the immune system and host-pathogen interactions and influence cytokine (IFN, TNF, and interleukin) signaling in response to bacterial and viral infections [38]. The miR-378 family was observed to influence cell proliferation, and to suppress tumour growth and angiogenesis through various signaling pathways and cytokine production patterns [39][40][41][42][43][44][45]. Our findings show that miR-29a increases IFN-β production and decreases the expression of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…miR-378b, a member of the miR-378 family, is highly conserved across species, from chimp to humans. A previous study has shown that miR-378b is expressed in normal human dermal fibroblasts, and circulating miR-378b is a sensitive biomarker for photo-aging (Joo et al, 2017). It was also found to protect dermal fibroblasts from UVB-inhibited collagen I by targeting SIRT6 (Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…In this sense, molecular circuits between miRNAs and EMT-TFs have been elucidated, such as that one involving miR-200 and ZEB1 [20]. Other examples involve miRNA-29, miRNA-378b, and miRNA-26a-5p, which are direct regulators of EMT and fibrosis through collagen expression by several mechanisms, such as by inhibiting sirtuin-6 and the autophagic protein ULK-1 [21][22][23]. Main molecular mechanisms underlying EMT activation.…”
Section: Noncoding Rnasmentioning
confidence: 99%